2015
DOI: 10.1080/1745039x.2015.1013666
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated parameters of subclinical ketosis on the immune system of dairy cows:in vivoandin vitroresults

Abstract: Using an established model in which subclinical ketosis is induced, the response of differential blood counts and levels of various haematological variables, including the inflammatory marker haptoglobin (Hp), were tested over the last six weeks of parturition until the 56th day post-partum in cows with lower or higher body condition scores (LBC and HBC, respectively; n = 9/group). Animals in the HBC group evidenced subclinical ketosis whereas LBC animals were metabolically healthy. For in vitro examination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 31 publications
6
33
0
Order By: Relevance
“…The WBC and RBC counts in the blood indicate immunological function of dairy cows (Schulz et al, 2015;Kvidera et al, 2017), and increased WBC and RBC counts in whole blood indicate an improved immunity (Schulz et al, 2015;Kvidera et al, 2017). In the present study, the quadratically increased WBC and RBC counts in blood suggested an improved immunity of dairy cows fed median levels of HMBSe (0.1 and 0.3 mg/kg).…”
Section: Discussionsupporting
confidence: 57%
“…The WBC and RBC counts in the blood indicate immunological function of dairy cows (Schulz et al, 2015;Kvidera et al, 2017), and increased WBC and RBC counts in whole blood indicate an improved immunity (Schulz et al, 2015;Kvidera et al, 2017). In the present study, the quadratically increased WBC and RBC counts in blood suggested an improved immunity of dairy cows fed median levels of HMBSe (0.1 and 0.3 mg/kg).…”
Section: Discussionsupporting
confidence: 57%
“…In this study, liver oxidative damage caused by high NEFA and low Glu suggested elevated plasma AST, GGT, and TBIL (3). In addition, a high plasma concentration of NEFA is temporally correlated with an impaired peripheral blood neutrophil function, which affects the response to immune challenges (21).…”
Section: Discussionmentioning
confidence: 99%
“…This energetic load was demonstrated by differences between primiparous and multiparous dairy cows in a number of metabolic parameters, milk yield, and body condition, as well as their inter-relationships (Wathes et al 2007). Accordingly, increased concentrations of BHB or isoproterenol (adrenaline-like substance) diminished the responsiveness of immune cells in a dose-dependent manner (Sempere et al 2004;Schulz et al 2015). In contrast, increased plasma concentrations of prolactin facilitated the in vitro proliferation of murine and human lymphocytes (Hartmann et al 1989).…”
mentioning
confidence: 99%